LEACHING STUDY OF SPHALERITE CONCENTRATE FROM CENTRAL KALIMANTAN IN SULPHURIC ACID MEDIUM USING OZONE AS OXIDIZING AGENT - Kooswara, Sherwin
Zinc (Zn) is a non-ferrous metal that is widely used in daily life. Zinc is mostly produced from primary sources, namely mineral sphalerite (ZnS) where the zinc extraction process from sphalerite is generally done through roast-leachelectrowinning (RLE) route. As an alternative to RLE route, zinc extraction method from sphalerite by hydrometallurgical route is developed which requires lower energy consumption and does not produce gas emissions and dust. In this research, Zn extraction from sphalerite concentrate was studied by leaching in sulphuric acid solution using ozone as oxidizing agent. The ozone injection system was designed based on the modification of the design proposed in the previous research. Sphalerite concentrate sample was received from a sphalerite flotation plant in Central Kalimantan. Series of leaching experiments were carried out on sphalerite concentrate in sulphuric acid solution using ozone as oxidizing agent. Experiments began with sample preparation, including drying, homogenization, sampling and sieving. The dominant mineral in the concentrate was identified by X-Ray Diffraction (XRD), while the chemical composition of the concentrate was analyzed by X-Ray Fluorescence (XRF). Leaching experiments were carried out using 50 grams concentrate per litre solution at room temperature for 12 hours with an oxygen injection rate of 1 litre per minute where ozon produced through an ozone generator by corona discharge method. The experimental variables studied were the concentrate size fraction, sulphuric acid concentration, and the height of the reactor for ozon injection. The percentage of Zn dissolved were periodically analyzed by Atomic Absorption Spectroscopy (AAS). In addition, leaching selectivity to iron, copper, and lead was also investigated. The leaching experiment results show that the concentrate size fraction used affects the percentage of Zn extraction obtained, whereas the fine concentrate size fraction gives better ozone solubility and higher Zn extraction. Increasing concentration of sulphuric acid from 0.5 M to 2M increases extraction of Zn, while a further increase of H2SO4 concentration from 2M to 4M decreases extraction of Zn due to the salting-out mechanism. The percentage of Zn extraction increases with the height of reactor for ozon injection used in leaching experiments due to the enhanced of ozone residence time in the slurry. The highest Zn extraction percentage of 92.86% was obtained from the experiment with concentrate size fraction of -325+400#, 2M sulphuric acid, the reactor height for ozon injection of 32 cm, stirring speed of 400 rpm, oxygen injection rate of 1 litre/minute and solid percentage of 50 grams/litre. At this condition, the Zn leaching selectivity to Fe, Cu and Pb were 0.69, 0.85 and 0.99, respectively (scale 0-1).